Isolation, Characterization of Zn Solubilizing Bacterium (Pseudomonas protegens RY2) and its Contribution in Growth of Chickpea (Cicer arietinum L) as Deciphered by Improved Growth Parameters and Zn Content. Issue 3 (9th August 2021) - Yasmin, Riffat; Hussain, Sabir; Rasool, Muhammad Hidayat; Siddique, Muhammad Hussnain; Muzammil, Saima
Background: Zinc is an essential micronutrient required for optimum plant growth. Zinc-solubilizing bacteria convert applied inorganic zinc to available forms that could be used by plants.Research design: In present study, experiments were conducted to isolate, characterize, and evaluate Zn solubilization potential of different bacteria.Results: Among 10 isolated strains, Pseudomonas protegens (RY2, MF351762) was found to be the most promising strain having zinc-solubilizing potential on 4 different insoluble zinc sources. In quantitative assay, Zn solubilization by RY2 was significantly higher than other strains at different incubation time. P. protegens RY2 was selected (based on zinc solubilizing and plant growth promoting activities like P solubilization and ACC deaminase) for plant experiments. Meanwhile, available Zn release rate in soil was determined at day 10 of incubation. Chickpea seeds were inoculated with RY2 strain and ZnO is used as zinc source. Growth parameters and quantifying zinc content of shoot and root using atomic absorption spectrophotometer were determined. Enhanced shoot and root dry weights and lengths were observed in chickpea plants compared to control. Maximum increase of 44%, 67%, and 75% in T2 (Soil + RY2), T5 (Soil + ZnO + RY2), and T7 (Soil + manure + ZnO + RY2), respectively, was found in shoot length compared to control (T1).Conclusion: The study indicated that zinc-solubilizing RY2 strain possesses potential for enhanced Zn in soil so it would allow reduced inorganic Zn application.